The Role of Public Policy Analyst in Public Organizations: An Assessed Applied Study in the Ministries of Education, Health and Social Development in Jordan - Rababah, Fatima; Abuqauod, Ghazi (Jordan Journal of Business Administration, 2020)
This study aims to analyze and assess the sub-dimensions of the role of public policy analyst (function, methodology, frameworks governing the role of the analyst, obstacles) in the Ministries of Education, Health and Social Development in Jordan from the viewpoint of analysts or practitioners of analytical roles. To achieve the objectives of the study, a questionnaire was developed and distributed to those who perform analytical roles totaling (102) respondents. (98) questionnaire forms were valid for statistical analysis, representing (96%) of the study population. Statistical Package for Social Studies (SPSS) was utilized to generate measurements for general mean, standard deviation and correlation. The study came to several conclusions, including that the general mean for the perceptions of analysts regarding the function of an analyst, methodology and frameworks governing the analyst’s role was moderate, while the average of the perceptions of analysts regarding the obstacles was high. The study shows the multiplicity of actors engaged in the work of analysis and the presence of multiple titles used by these actors. The study also shows a strong correlation relationship between the function of an analyst and frameworks governing the role of the analyst. The study also shows a weak correlation relationship between the obstacles to the role of the analyst and the frameworks governing the role of the analyst. The study recommended the need to work on the development of the legislative terms that explicitly determine the role of the analyst, unite those involved in the process of analysis at the state level through the establishment of a national professional institution and standardize the titles of individuals who are exercising the role of the analyst, in addition to developing a model for a policy analyst worksheet that includes the main aspects of the role of the analyst and providing an archival system of various former public policies and previous results or the formation of an information system for public policy analysis.